GAMBARAN INTERAKSI SOSIAL SUKU JAWA DAN SUKU SUNDA - Aironi Zuroida; Husni Anggoro; Ilham Yusril Ramadhan (PSIKOWIPA (Psikologi Wijaya Putra), 2022)
The purpose of this study is to describe how the social interaction of variables between the Javanese and Sundanese are. This study uses a literature review method where from 15 literature the author determines 6 literatures studied and according to the topic of this research. The results of the study explain that the identity of the Javanese and Sundanese are almost the same as evidenced by the Javanese, whose attitude is that the Javanese are friendly, that is, they have good relations with anyone, while the Sundanese are friendly and easy to get along with. However, in social interaction they certainly still have obstacles including differences in accent, language, and habits. However, this can be overcome considering the attitude of the Sundanese and Javanese who want to interact with everyone, are friendly and easy to get along with.